ANALISA PENGARUH SUDUT BELOKAN PENSTOK TERHADAP DAYA KELUARAN PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) - Riza Syammajid Khoirudin (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2019)
Research on penstock turn angle analysis on power in generators. Turning angles are determined at 300, 450 and 600 on the penstock channel. The author conducted a study to examine the effect of the penstock turn angle on the generator output power in a Micro Hydro Power Plant (MHP).The research phase was carried out by establishing the research model, parameters determined at the turning angle of the PLTMH penstock include water discharge, penstock diameter and the manning coefficient. The next step is calculating the head minor, major head, total head, effective head and determine the output power of the MHP generator.The results show that the output power at PLTMH with the effect of the turning angle contained in the penstock is At an angle of 300 the power obtained is P = 384.91 kW. At an angle of 450 the potential power obtained is P = 383.41 kW. At an angle of 600 the power obtained is P = 380.93 kW. So the turning angle mounted on the penstock Power produced is equal to 384.91 kW with a bend angle of 300.Keywords : PLTMH, Penstock Pipes, Angles